The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313471
|View full text |Cite
|
Sign up to set email alerts
|

Learning Resolution Parameters for Graph Clustering

Abstract: Finding clusters of well-connected nodes in a graph is an extensively studied problem in graph-based data analysis. Because of its many applications, a large number of distinct graph clustering objective functions and algorithms have already been proposed and analyzed. To aid practitioners in determining the best clustering approach to use in different applications, we present new techniques for automatically learning how to set clustering resolution parameters. These parameters control the size and structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Finally, we note that there are more general constructions possible. For instance, differential penalties for S and S in the localized cut graph can be used for a variety of effects [Orecchia and Zhu, 2014;Veldt et al, 2019b]. For 1-norm objectives, optimal parameters for γ and κ can also be chosen to model desierable clusters [Veldt et al, 2019b] -similar ideas may be possible for these p-norm generalizations.…”
Section: R E L At E D W O R K a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we note that there are more general constructions possible. For instance, differential penalties for S and S in the localized cut graph can be used for a variety of effects [Orecchia and Zhu, 2014;Veldt et al, 2019b]. For 1-norm objectives, optimal parameters for γ and κ can also be chosen to model desierable clusters [Veldt et al, 2019b] -similar ideas may be possible for these p-norm generalizations.…”
Section: R E L At E D W O R K a N D Discussionmentioning
confidence: 99%
“…For instance, differential penalties for S and S in the localized cut graph can be used for a variety of effects [Orecchia and Zhu, 2014;Veldt et al, 2019b]. For 1-norm objectives, optimal parameters for γ and κ can also be chosen to model desierable clusters [Veldt et al, 2019b] -similar ideas may be possible for these p-norm generalizations. We view the structured flexibility of these ideas as a key advantage because ideas are easy to compose.…”
Section: R E L At E D W O R K a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In follow up work [10], the same authors showed that the LambdaCC LP relaxation has an O(log n) integrality gap. They also later proved new results for how learn the best value of λ to use in practice [34].…”
Section: Related Workmentioning
confidence: 88%
“…Our ability to approximate the LP relaxation of a clustering objective in all parameter regimes is useful even when LP solutions are not rounded to produce approximate clusterings. Solutions to the LP provide lower bounds for evaluating the performance of heuristic clustering techniques, and can also be useful for learning how to set graph clustering resolution parameters in practice [34].…”
Section: Overview Of Contributionsmentioning
confidence: 99%